2021
DOI: 10.34117/bjdv7n2-022
|View full text |Cite
|
Sign up to set email alerts
|

Perfil Epidemiológico De Escorpionismo No Nordeste Brasileiro (2009 a 2019)/ Epidemiological Profile of Scorpionism in Northeast Brazil (2009 to 2019)

Abstract: anos (147.080) e ensino fundamental incompleto (90.482). Faz-se necessário a implementação de políticas públicas voltadas à educação em saúde.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
1
0
3
Order By: Relevance
“…The accidents by scorpions predominantly involved women in the municipality of Natal, but the greatest risk of complications occurs in men. In the literature, the fact that women are more affected by scorpion stings has been reported in the Northeast of Brazil, such as the states of Ceará [ 12 ] and Piauí [ 39 , 40 ], corroborating with our data. In the state of Pará, located in the Northern region of Brazil, it was found that there is a difference in the sex most affected by scorpionism and that men are more subject to the accident [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…The accidents by scorpions predominantly involved women in the municipality of Natal, but the greatest risk of complications occurs in men. In the literature, the fact that women are more affected by scorpion stings has been reported in the Northeast of Brazil, such as the states of Ceará [ 12 ] and Piauí [ 39 , 40 ], corroborating with our data. In the state of Pará, located in the Northern region of Brazil, it was found that there is a difference in the sex most affected by scorpionism and that men are more subject to the accident [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Cases ignored regarding race/color were common in 79 cases (27.3%) (graph 2). Several academic studies have already demonstrated a higher occurrence of Chagas disease in brown people (ALENCAR MMF, et al, 2020;CARDOSO LP, et al, 2020;FELIX EBG, et al, 2020;SILVA GG, et al, 2020;OLIVEIRA SS, et al, 2021;SOUZA SB, et al, 2021;VILHENA AO, et al, 2020), demonstrating that the epidemiological profile in that city does not differ from the rest of Brazil. Such inferences are associated with the self-declaration of the Brazilian population regarding their skin color, where around 76.5% of the population declared themselves black and/or mixed race (IBGE, 2010).…”
Section: Resultsmentioning
confidence: 96%
“…Além disso, com relação à faixa etária, indivíduos de 20 a 39 anos foram os mais acometidos. Todavia, crianças com até 4 anos de idade e idosos acima de 70 anos, representam o grupo populacional mais suscetível às complicações graves pelo escorpionismo, em virtude da vulnerabilidade de seu sistema imunológico (Oliveira et al, 2021).…”
Section: R E S U M Ounclassified